The Impelementation of Genre-Based Approach to Improve Students’ Reading Comprehension of Descriptive Text - Yohanes Gatot Sutapa Yuliana; Indah Octaviani; Yanti Sri Rezeki (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The basis for this research was the student’s difficulties with reading comprehension. The aim of this research was to investigate the effect of using a Genre-based approach on student’s ability to comprehend descriptive text better. This research was carried out at SMPN 4 Sungai Raya on the eighth-grade students in class D in the academic year 2017/2018. The results of this research showed that, following the application of the Genre-based approach, students’ reading comprehension of descriptive text improved. In addition, the approach’s application enhanced the students’ positive responses to the learning activities, which in turn improved students’ learning interest toward reading. To summarize, the research findings proved that the implementation of a Genre-based approach improves the student’s reading comprehension of descriptive text in the eighth-grade students of SMPN 4 Sungai Raya Kabupaten Kubu Raya in the academic year 2017/2018.